Computer graphics with openGL - Hearn, Donald; Baker, M.Pauline; Carithers, Warren R. (USA : Prentice Hall, 2011)
A survey of computer graphics, computer graphics hardware, computer graphics software...
Keywords: Computer graphics; OpenGL